2019
DOI: 10.1111/apt.15127
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms underlying effects of kiwifruit on intestinal function shown by MRI in healthy volunteers

Abstract: Summary Background Chronic constipation affects approximately 17% of the population worldwide and remains an important unmet need since patients are often dissatisfied with treatment. Kiwifruit may offer an alternative to traditional laxatives and have been shown to increase stool volume, frequency and improve consistency. Aims Using non‐invasive MRI techniques, we assessed the effect of ingestion of kiwifruit on fluid distribution in the intestines and bowel function. Methods Two period crossover trial of kiw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 29 publications
1
42
1
Order By: Relevance
“…Previous studies using radiopaque markers have shown that green kiwifruit accelerates whole gut transit time in patients with constipation and constipation‐predominant irritable bowel syndrome 2‐4 . In a recent study from Nottingham using MRI in healthy subjects, the authors found that ingestion of two green kiwifruits per day, the same intake as we used in the present study, produced an increment in water content in the small bowel and the ascending colon that could account for the increment in stool frequency and looser stool consistency observed 14 . However, in this study, the authors found the increment in colonic contents induced by kiwifruit, smaller than the increment induced by intake of psyllium in previous studies.…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…Previous studies using radiopaque markers have shown that green kiwifruit accelerates whole gut transit time in patients with constipation and constipation‐predominant irritable bowel syndrome 2‐4 . In a recent study from Nottingham using MRI in healthy subjects, the authors found that ingestion of two green kiwifruits per day, the same intake as we used in the present study, produced an increment in water content in the small bowel and the ascending colon that could account for the increment in stool frequency and looser stool consistency observed 14 . However, in this study, the authors found the increment in colonic contents induced by kiwifruit, smaller than the increment induced by intake of psyllium in previous studies.…”
Section: Discussionsupporting
confidence: 56%
“…Previous studies from other laboratories have shown that psyllium and high‐calorie meals delay gas transit and evacuation 12,13 . In addition, trapping of gas by viscous material, as has been described for water after intake of a similar quantity of kiwifruit, 14 could delay gas transit and produce gas‐related abdominal symptoms. On the other hand, a prokinetic effect of kiwifruit 5 could accelerate transit and removal of intestinal gas, and thereby prevent gas‐related abdominal symptoms while improving constipation.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Respectively the T2 values in the ascending colon of the healthy group were 70 (56–72) ms, 73 (62–86) ms, and 83 (67–88) ms and T2 in the descending colon were 53 (40–67) ms, 54 (45–70) ms, and 74 (56–80) ms. The T2 of the patients’ ascending colon was 58 (42–73) ms on maltodextrin and 72 (51–105) ms on psyllium, while the respective values for the descending colon were 42 (34–52) ms and 66 (54–86) ms. Also, in a study of kiwifruit supplementation [32], the AUC (in seconds×minute units of measure) of the T1 constant of the ascending colon was 356 ± 109 on kiwifruit intervention and 291 ± 110 on control at time = 0–420 min whereas the AUC of the T1 from 240 to 420 min was 137 ± 39 and 108 ± 40, respectively. For the descending colon, the respective values were 216 ± 120 and 203 ± 114 from 0–420 min and 96 ± 50 and 87 ± 52 from 240–420 min.…”
Section: Colonic Chyme and Fluidmentioning
confidence: 99%
“…Two kiwifruits taken twice daily demonstrate an immediate increase in small bowel water following consumption, which increases steadily throughout the day only falling after a second large meal which stimulates ileal emptying into the ascending colon. This was associated with a rise in ascending colon T1, indicating increased water content caused by increased inflow of ileal fluid [41].…”
Section: Effect Of Phytochemicalsmentioning
confidence: 99%